Volatile Molecules Secreted by the Wheat Pathogen Parastagonospora nodorum Are Involved in Development and Phytotoxicity - Muria-Gonzalez, Mariano Jordi; Yeng, Yeannie; Breen, Susan; Mead, Oliver; Wang, Chen; Chooi, Yi-Heng; Barrow, Russell A.; Solomon, Peter S. (Frontiers in Microbiology, 2020)
Septoria nodorum blotch is a major disease of wheat caused by the fungus Parastagonospora nodorum. Recent studies have demonstrated that secondary metabolites, including polyketides and non-ribosomal peptides, produced by the pathogen play important roles in disease and development. However, there is currently no knowledge on the composition or biological activity of the volatile organic compounds (VOCs) secreted by P. nodorum. To address this, we undertook a series of growth and phytotoxicity assays and demonstrated that P. nodorum VOCs inhibited bacterial growth, were phytotoxic and suppressed self-growth. Mass spectrometry analysis revealed that 3-methyl-1-butanol, 2-methyl-1-butanol, 2-methyl-1-propanol and 2-phenylethanol were dominant in the VOC mixture and phenotypic assays using these short chain alcohols confirmed that they were phytotoxic. Further analysis of the VOCs also identified the presence of multiple sesquiterpenes of which four were identified via mass spectrometry and nuclear magnetic resonance as β-elemene, α-cyperone, eudesma-4,11-diene and acora-4,9-diene. Subsequent reverse genetics studies were able to link these molecules to corresponding sesquiterpene synthases in the P. nodorum genome. However, despite extensive testing, these molecules were not involved in either of the growth inhibition or phytotoxicity phenotypes previously observed. Plant assays using mutants of the pathogen lacking the synthetic genes revealed that the identified sesquiterpenes were not required for disease formation on wheat leaves. Collectively, these data have significantly extended our knowledge of the VOCs in fungi and provided the basis for further dissecting the roles of sesquiterpenes in plant disease.